Cosserat elasticity of negative Poisson's ratio foam: experiment. (8th April 2016) - Rueger, Zach; Lakes, Roderic S
Abstract: Negative Poisson's ratio polymer foams derived from reticulated open cell foams exhibit large size effects in torsion and bending. Effective moduli increase as diameter decreases in contrast to the prediction of classical elasticity. Size effects of this sort are predicted by Cosserat (micropolar) elasticity in which points can rotate as well as translate and distributed moments are incorporated. The Cosserat coupling number N was about twice as large as that of as-received foam, leading to strong effects. The torsion characteristic length ℓ t was similar. Cosserat effects are known to enhance toughness and immunity from stress concentration.